Clostridium difficile versus general gastroenteritis: A critical review of a concept - Azadeh Nasrollah; Shiva Hashemi; Parvin Talebloo; Mehdi Rajabi (Archives of Global Professionals, 2016)
Objective: Clostridium difficile is the most important definable cause of healthcare-acquired diarrhea which is mostly associated with inappropriate use of broad-spectrum antibiotics. Recommended treatments for C. difficile infection (CDI) are metronidazole, oral vancomycin, and fidaxomicin (a new narrow spectrum macrocyclic antibiotic). The aim of this investigation was to review the chosen management of general gastroenteritis against risks associated with inappropriate therapeutic options such as CDI in the largest teaching medical school in Iran. Methods: Two thousand medical records and prescriptions were scrutinized, between March 2012 and July 2013 in Phase 1 and September 2014-January 2015 in Phase 2 for patients complaining of diarrhea, colitis, and gastroenteritis. The therapeutic route was investigated in each individual case bearing in mind the medical and medication history as well as other comorbidities. The selection of antibiotic by many medical practitioners for the treatment of mentioned complaints was inappropriate and random. Results: In most cases, the chosen antibiotic can itself be associated with initiation or worsening of CDI. Although there is no official report on resistance to metronidazole or oral vancomycin at this stage, this unrestricted antibiotic use must be addressed. Conclusions: The needs for antimicrobial stewardship programs to preserve the effectiveness of current available therapies are strongly recommended. This program must focus on the overall reduction of inappropriate antibiotic prescribing and ultimately on enforcing the adherence to the reputable antibacterial guidelines.